Urban Mining Systems - Nakamura, Takshi (Springer, 2015)
This book focuses on the fundamental concept of and current endeavors in “urban mining” among those who are interested in both metal resources and ecology. Systems for recycling and reusing precious metals and rare-earth minerals contained in used and discarded electronics are introduced in this book. The target audience is not academic researchers in the resource management and ecology fields but, rather, citizens who are concerned about our future environment and want to do something for the future.